2022
DOI: 10.3389/fonc.2022.939891
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a DNA repair-related gene signature with potential implications for prognosis and therapeutic response in pancreatic adenocarcinoma

Abstract: BackgroundPancreatic adenocarcinoma (PAAD) is one of the leading causes of cancer death worldwide. Alterations in DNA repair-related genes (DRGs) are observed in a variety of cancers and have been shown to affect the development and treatment of cancers. The aim of this study was to develop a DRG-related signature for predicting prognosis and therapeutic response in PAAD.MethodsWe constructed a DRG signature using least absolute shrinkage and selection operator (LASSO) Cox regression analysis in the TCGA train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Breast cancer patients with high RECQL5 expression have a negative prognosis [ 62 ]. Lower OS is linked to increased expression of RECQL, BLM, and WRN in pancreatic cancer [ 63 , 64 , 65 ]. However, there has been limited research on the clinical significance of RECQL4 in LIHC.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients with high RECQL5 expression have a negative prognosis [ 62 ]. Lower OS is linked to increased expression of RECQL, BLM, and WRN in pancreatic cancer [ 63 , 64 , 65 ]. However, there has been limited research on the clinical significance of RECQL4 in LIHC.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies have shown that several molecular are capable to distinguish whether the cancers are sensitive to oxaliplatin-based chemotherapies. Lai et al [ 7 ] constructed a three DNA repair-related genes signature (RECQL, POLQ, and RAD17) to predict the prognosis of pancreatic cancer, and RAD17 expression is correlated with oxaliplatin treatment. We previous using gene profiles datasets to establish predictive model for the CRC prognosis, and constructed a oxaliplatin related-gene model and showed good predictive value on CRC prognosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%